MOTIF MENONTON PROGRAM BERITA ISLAMI MASA KINI TRANS TV TERHADAP TINGKAT KEPUASAN PADA JAMAAH MASJID RAYA ANNUR DI KOTA PEKANBARU - Dina Oktamirantika; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed to determine how much the motive to watch programme Berita Islami Masa Kini Trans Tv against satisfaction on Annur Great Mosque Pilgrims at Pekanbaru and to determine which motif that take bigger influence against satisfaction of watching on Annur Great Mosque at Pekanbaru.The methods of this research is using quantitative methods with descriptive explanation. Data collection technique using questionnaire with 100 respondent. Researcher use a simple regression analysis to determine how much influence between the two variables.The result shown that the motive of watching programme Berita Islami Masa Kini Trans Tv is appreciable against satisfaction of watching that obtained by Annur Great Mosque Pilgrims. And the motive that take bigger influence against satisfaction of watching is the information motive, which percentage for this category about 56% at all.Keyword : motive of watching, television programme, satisfaction of watching